Quality and quantity of serious violent suicide attempts during the COVID-19 pandemic - Maleitzke, Tazio; Zocholl, Dario; Topp, Tobias; Dimitrov-Discher, Annika; Daus, Elly; Reaux, Gabriel; Zocholl, Malin; Conze, Rolf Nicolas; Kolster, Moritz; Weber, Philipp; Fleckenstein, Florian Nima; Scheutz Henriksen, Louise; et al. (Frontiers in Psychiatry, 2022)
Background: While repeated shutdown and lockdown measures helped contain the spread of Sars-CoV-2 during the Covid-19 pandemic, social distancing and self-isolation negatively impacted global mental health in 2020 and 2021. Although suicide rates did reportedly not increase during the first months of the pandemic, long-term data, and data on the quality of serious violent suicide attempts (SVSAs) are not available to date. Materials and Methods: Orthopedic trauma patient visits to the emergency department (ED), ED trauma team activations, and SVSAs were retrospectively evaluated from January 2019 until May 2021 in four Level-I Trauma Centers in Berlin, Germany. SVSAs were assessed for suicide method, injury pattern and severity, type of treatment, and length of hospital stay. Results: Significantly fewer orthopedic trauma patients presented to the ED during the pandemic (n=70,271) compared to the control (n=84,864) period (p=0.0017). ED trauma team activation numbers remained unchanged. SVSAs (corrected for seasonality) also remained unchanged during control (n=138) and pandemic (n=129) periods, and no differences were observed for suicide methods, injury patterns, or length of hospital stay. Conclusion: Our data emphasize that a previously reported rise in psychological stress during the Covid-19 pandemic does not coincide with increased SVSA rates or changes in quality of SVSAs.